IMF Survey, Volume 35, Issue 20. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
Murilo Portugal, Agustin Carstens, Kyrgyz Republic, HIPC, central Asia, Indonesian debt, Saudi Arabian economy, Peter Kenen, European Central Bank, ECB, Danish economy, flexicurity,Burundi's economy, aid volatility, Indian and China, Doing Business.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet